Front Cover: Towards Sustainable High‐Performance Thermoplastics: Synthesis, Characterization, and Enzymatic Hydrolysis of Bisguaiacol‐Based Polyesters (ChemSusChem 15/2018). Issue 15 (2nd August 2018) - Curia, Silvio; Biundo, Antonino; Fischer, Isabel; Braunschmid, Verena; Gübitz, Georg M.; Stanzione, Joseph F.
Abstract : The Front Cover shows how bisguaiacol (BG), a lignin‐derived bisphenol, can be used to prepare useful polyesters. Waste from the wood and paper industry (symbolized here by a Quercus Rubra log) can be utilized as a source of phenolic compounds for the synthesis of BG, which, in turn, can be used as a monomer for the preparation of polyesters. The products exhibit remarkable thermal properties, high‐temperature stability, and enzymatic hydrolysis susceptibility. The green arrows represent this cycle: derivatization from wood waste, polymerization to afford thermoplastics, and biodegradation leading to monomer release. More information can be found in the Full Paper by Curia et al. onpage 2529 in Issue 15, 2018 (DOI:10.1002/cssc.201801059 )